The economics and financing of media companies - Picard, Robert G. (Fordham University Press, 2011)
In this updated and expanded edition of the acclaimed Economics and Financing of Media Companies, leading economist and media specialist Robert G. Picard employs business concepts and analyses to explore the operations and activities of media firms and the forces and issues that affect them.